Inventory of coastal land use systems in the Mekong Delta, Vietnam : (Wageningen Agricultural University, 1996)
This report is written for the project MHO-8 IMCR (Integrated Management of Coastal Resources in the Mekong Delta, Vietnam). This project is a cooperation of WAU, The Netherlands and CTU, Vietnam. The Mekong Delta is the most productive agricultural area of Vietnam. At the moment some problems are threatening this area and so the income of many farmers, the food security and agriculture based export earnings. These problems are particularly severe in the coastal zone, characterised by shortage of fresh water, salt water intrusion, acid sulpahte soil, decreasing shrimp yields and low prices for rice.